The Influence of Audit Opinion and Managerial Ownership on Income Smoothing in Banking Companies - Dyah Resti Utami; Einde Evana; Yuliansyah Yuliansyah (Universitas Prasetiya Mulya, 2020)
This research was conducted on banking companies that are included in the top 30 in Indonesia. Data analysis method used in this study is to use a descriptive statistical analysis and logistic regression method with data processing using SPSS 21. The results of this study indicate that audit opinion has a negative but not significant effect on income smoothing. This indicates that with a low audit opinion does not indicate the company is making income smoothing. Managerial ownership shows the results have a significant negative effect on income smoothing, this indicates that the ownership of shares in the company can reduce the actions of managers to make income smoothing.Keywords:Audit opinions, Managerial ownership, Income smoothing* Accounting Departement, Faculty of Business and Economics, University of Lampung, Jl. Prof. Dr. Ir. Sumantri Brojonegoro, Gedong Meneng, Kec. Rajabasa, Kota Bandar Lampung, Lampung 35141, Indonesia https://doi.org/10.21632/irjbs.13.1.15-26